Improving mother’s skills in the technology of making main foods and healthy snacks and the nutritional status of pre-school children: - - Widia Ilmiah; Fifin Maulidatul Azizah (Universitas Nahdlatul Ulama Surabaya, 2022)
Indonesia's child nutrition problem is becoming a national health problem. Food technology is expected to be a solution. Five-year-olds' nutritional status data was thin and very thin in 2013 (12.1%), in 2018 (10.2%). Preliminary study results in Al Hidayah Kindergarten were known from 5 mothers showing 4 people (80%) do not know how to process, serve the main food and make healthy snacks for their children. The aim is to analyze improving mother's skills in the technology of making main foods and healthy snacks and the nutritional status of pre-school children. Methods were preexperimental research design type one group pre-posttest design. The populations were all mothers and children in Sumbersecang Kindergarten were 42 people, the samples were 16 people, simple random sampling, instruments using questionnaires, checklists, counseling sheets, weight scales, analysis using paired t-test with SPSS v.16. The results that 68.8% of mothers age 21-40 years, 43.8% educated in elementary school, 81.3% not employed, 56.3% have an income of less than IDR.1,000,000,-, 50% of Madura tribe, 50% have a good level of knowledge, 31.3% of mother skills increase after the intervention, 31.3% of children are obese, their weight gain after intervention decreases by 25% and does not experience weight loss as much as 6.3%. Statistical test (p-value = 0.000 <α 0.05). The technology of making main foods and healthy snacks can improve the mother's skills and nutritional status of pre-school children and level of education, socioeconomic, level of knowledge become supporting factors.